Load bearing properties of composite masonry constructed with recycled building demolition waste and cement stabilized rammed earth. (15th January 2016) - Jayasinghe, C.; Fonseka, W.M.C.D.J.; Abeygunawardhene, Y.M.
Highlights: Concrete waste from BDW can be recycled and reused in manufacturing a building block. The concrete waste has been mixed with cement and soil to form a composite of BDW and SRE. The mix proportion of 1:5:5 cement, soil, concrete waste has been identified as the optimum mix proportion. The characteristic compressive strength in excess of 1.7 N/mm 2 was obtained for wall samples tested. The flexural strength with comparable results has been obtained for the composite of BDW and SRE. Abstract: Accumulation of construction waste is becoming a major environmental concern in developing countries since it ends up as piled landfills. Innovation of sustainable construction materials through recycling of such waste appears to be a viable solution to this problem. Recycled construction materials will also be an economical option in designing green buildings. The aim of the research is to introduce a building material manufactured out of Building Demolition Waste (BDW) mixed with soil and cement. Waste materials coming out of concrete elements were selected for the study and they were crushed and sieved through 10–15 mm and 15–20 mm sizes separately. Concrete waste was selected for the detailed investigations based on literature review and the performance of several trials. A mix proportion was selected based on the standard testing for grading of aggregate. The processed building demolition waste (BDW) was mixed with cement stabilized rammed earth (CSRE). The optimum proportion of construction waste, soil and cement was established using experimental results on cube testing. The recommended mix proportion was used to construct the wall panels for compressive and flexural testing. Based on the detailed experimental programme, compressive and flexural strength of the composite material, BDW and CSRE is found to be comparable with that of similar conventional materials. The load bearing properties of the composite material have been found satisfactory, for general masonry applications involving single and two storey houses thus indicating the possibility of combining BDW with CSRE to form another greener building material.